EFEKTIFITAS KONSELING KELOMPOK DENGAN TEKNIK RESTRUKTURISASI KOGNITIF UNTUK MEREDUKSI PERILAKU MEROKOK SISWA - Churniyawati, Retna; Yuhenita, Nofi Nur; Putro, Hijrah Eko (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
This study aims to test the effectiveness of group counseling with cognitive restructuring techniques to reduce students' smoking behavior. This study uses a true experimental design using the pretest-posttest control group design method. The sample taken in this study was 10 people consisting of 5 people in the experimental group with cognitive restructuring techniques and 5 people in the control group without intervention. Sampling using purposive sampling technique. The data collection method was carried out using a questionnaire on smoking behavior in students. The data analysis method used Non-Parametric Statistical Tests. The results of this study indicate that group counseling with cognitive restructuring techniques can reduce students' smoking behavior. This is evidenced by the results of the Mann Whitney Parametric Statistical test with an Asymp.Sig value. (2-Tailed) of 0.044 <0.05 where the hypothesis is stated to be accepted. Based on the results of the analysis and discussion, there is a difference in the average scores of the two groups. The experimental group had a percentage decrease of 31.82% while the control group was 20.23%. The conclusion in this study is that group counseling with cognitive restructuring techniques is more effective in improving cognitive restructuring than conventional group counseling.